HERBEL THERAPY PRACTICE FOR LOCALL LIVESTOCK : HERBEL THERAPY PRACTICE FOR LOCALL LIVESTOCK (Iraqi Journal of Market Research and Consumer Protection, 2023)
The herbs have a huge role in development of pharmacology besides the role of veterinary medicine in development of human medicine The study aimed to evaluate the therapeutic efficacy of pomegranate peel and leaves of both thuja and tobacco in 5 cows, 15 sheep and 15 goats were brought to veterinary clinics on the outskirts of Baghdad suffering from health problems in the skin, upper respiratory tract and digestive system. Cases were treated topically or orally as a powder, aqueous solution, or ointment. The results showed that 66% of cases were cured. The cure rate was related to the severity of the infection or lesion, course of treatment, routes of administration and herbal formula. Also, the results did not show any side effects of the herbal during the treatment period. Pour- on using of tobacco leaf infusion for lice-infected goats gave a better result than in sheep. The thuja and peels of pomegranate have proven to healing as an ointment for wounds, sores and blisters. Also, the aqueous solution or powder of thuja and peel of pomegranate have proven effective in reducing symptoms in the digestive system and upper respiratory disorders. Both ointments of thuja and pomegranate gave acceptable results for the treatment of warts (papilloma). Therefore, the farmer can use these herbs in emergencies. Recommendation is conducting more clinical veterinary studies on pomegranate, thuja, and tobacco leaves and their medicinal propriety. Thus, the field of veterinary medicine is the best field for reviving biopharmaceutical research and comparative medicine.